New organizational and legal forms (types) of the organizations in the budgetary sector of economy (Путеводитель предпринимателя, 2020)
In work need of reduction of the legislation in compliance by elimination of gaps locates in the sphere of fixing ofconcept of «the subject of managing» according to signs individualizing it, and also need of allocation of autonomous establishment in separate the organizational and legal form (OLF) that will promote more successful process of application of types of NPO, and, including, autonomous establishments.